Implementation of the principles of Fiqh Muamalah in the practice of daily life in today’s modern era - Idris, Moh (Maliki Interdisciplinary Journal, 2024)
Muamalah fiqh is an important part of Islamic teachings that regulates the procedures for economic activities. In muamalah, there are principles that must be adhered to, such as justice, the prohibition of usury, and cooperation in achieving the common good. Understanding and applying these principles is key to creating a just and economically sustainable society, in accordance with the teachings of the Islamic religion.